2010
DOI: 10.1103/physrevb.81.035327
|View full text |Cite
|
Sign up to set email alerts
|

Calculating the trap density of states in organic field-effect transistors from experiment: A comparison of different methods

Abstract: The spectral density of localized states in the band gap of pentacene (trap DOS) was determined with a pentacene-based thin-film transistor from measurements of the temperature dependence and gate-voltage dependence of the contact-corrected field-effect conductivity. Several analytical methods to calculate the trap DOS from the measured data were used to clarify, if the different methods lead to comparable results. We also used computer simulations to further test the results from the analytical methods. Most … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
281
2
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(303 citation statements)
references
References 64 publications
18
281
2
2
Order By: Relevance
“…charge transport has been proposed and widely accepted, 13,14 and there have been many attempts to determine the trap density of states (trap DOS). However, the trap DOS has been analyzed mainly for p-channel materials, [13][14][15][16][17][18][19][20] and comparatively limited works have been done for n-channel materials. 15,[21][22][23] In particular, the trap DOS has not been systemically studied from the viewpoint of the basic transistor operation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…charge transport has been proposed and widely accepted, 13,14 and there have been many attempts to determine the trap density of states (trap DOS). However, the trap DOS has been analyzed mainly for p-channel materials, [13][14][15][16][17][18][19][20] and comparatively limited works have been done for n-channel materials. 15,[21][22][23] In particular, the trap DOS has not been systemically studied from the viewpoint of the basic transistor operation.…”
Section: Introductionmentioning
confidence: 99%
“…Lang et al have extracted the trap DOS from the Arrhenius plot of the transconductance for single-crystal pentacene transistors, 32,33 and similar analysis has been applied to other thin-film organic semiconductors. 15,16 In addition, a variety of methods to calculate the trap DOS have been investigated, and an exponential distribution of the DOS has been established in pentacene thin-film transistors, [17][18][19] and in single crystal transistors. 20 The DOS distribution has been also extracted from space-charge-limited-current spectroscopy and Kelvin probe microscopy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its advantage over most other methods of DOS extraction is that it does not require temperature dependent measurements while producing comparable results to other methods. 31 The DOS analysis relies on two main assumptions: firstly that transport through the material is limited by multiple trapping and thermal release, 32,33 and secondly that there is a conduction band edge, above which the conduction band DOS is assumed to be constant with fixed electron mobility and below which exists only traps that produce a localized bandgap DOS. These bandgap states control the subthreshold characteristics of a TFT and the measured field effect mobility via the relative fraction of charge carriers distributed in immobile and mobile states.…”
Section: Bandgap Density Of States (Dos) Analysismentioning
confidence: 99%
“…Note that in the ME model, we construct the band-tail states using a superposition of a half-Gaussian and an exponential distribution. We attribute the overall fitting distribution widths of 2 to 5 k B T, indicated in Table 1, to structural defects and chemical impurities 1 , previously reported for small organic molecules 3,53,54 . A recent study 55 , and compared it to the evolution observed in the UPS measurements.…”
mentioning
confidence: 99%